Rural industrialisation its dynamic and local linkages - Eapen, Mridul (New Delhi Manohar, 2001)
The author focusses on the role of rural linages in sustainingthe process of rural industrialization in kerala.The main contents of the book are-spatial spread of industrial activity in Kerala,size structure of manufacturing industry in Kerala and growth
Keywords: Rural industries-India-Kerala; Industries-India-Kerala